2020
DOI: 10.5114/fn.2020.102433
|View full text |Cite
|
Sign up to set email alerts
|

A link between promoter polymorphisms of the transforming growth factor β1 (TGFB1) and TGF-β1 receptor II (TGFBR2) genes and relapsing-remitting multiple sclerosis

Abstract: Introduction: Multiple sclerosis (MS) is a chronic progressive autoimmune disease characterised by nerve demyelination, mediated by myelin-specific Th1 autoreactive cells. Transforming growth factor β1 (TGF-β1) is a regulatory cytokine involved in MS aetiology by maintaining CD4+ cell differentiation and preventing autoimmune responses. Because of the important role of the TGF-β1 signalling pathway in MS aetiopathogenesis, we aimed to investigate the association of two DNA polymorphisms: TGFB1C[-509]T and TGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
0
2
Order By: Relevance
“…No entanto, alguns estudos investigaram outras doenças. Grigorova et al (27) avaliaram a associação entre o polimorfismo rs1800469 do gene TGFB1 e o polimorfismo rs3087465 do gene TGFBR2 e episódios frequentes de atividade da doença em pacientes com esclerose múltipla. Os autores observaram maior concentração de TGFB1 determinada pelo genótipo TGFB1 em combinação com o genótipo TGFBR2 e concluíram que essa combinação atuou como fator protetor contra a esclerose múltipla remitente-recorrente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No entanto, alguns estudos investigaram outras doenças. Grigorova et al (27) avaliaram a associação entre o polimorfismo rs1800469 do gene TGFB1 e o polimorfismo rs3087465 do gene TGFBR2 e episódios frequentes de atividade da doença em pacientes com esclerose múltipla. Os autores observaram maior concentração de TGFB1 determinada pelo genótipo TGFB1 em combinação com o genótipo TGFBR2 e concluíram que essa combinação atuou como fator protetor contra a esclerose múltipla remitente-recorrente.…”
Section: Discussionunclassified
“…Os autores observaram maior concentração de TGFB1 determinada pelo genótipo TGFB1 em combinação com o genótipo TGFBR2 e concluíram que essa combinação atuou como fator protetor contra a esclerose múltipla remitente-recorrente. (27) Jin et al (28) analisaram a associação entre os polimorfismos supracitados e o carcinoma de células escamosas do esôfago. Os autores concluíram que indivíduos portadores de genótipos variantes desses polimorfismos apresentavam risco significativamente reduzido de carcinoma de células escamosas do esôfago.…”
Section: Discussionunclassified
“…The risk of gastric cancer was notably lower among subjects who carried both the TGF-Β1 -509C and TGF-ΒR2 -875A allele genotypes. We also demonstrated that a combination of TGF-Β1T [-509] T with the TGF-ΒR2G [-875] A genotype might be a protective factor against relapsing-remitting multiple sclerosis development in men[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed the genotyping of the TGF-ΒR2 G [-875] A (rs3087465) by primer-introduced restriction analysis-polymerase chain reaction (PCR) assay[ 15 ]. The primer sequences were the following: forward primer- 5’-GCAAGAAAGGAAATTTGA AAGTTTGT-3’ and reverse primer 5’-TCACCTGAATGCTTGTGCTTTT-3’.…”
Section: Methodsmentioning
confidence: 99%